PENGARUH TEKNIK KUNJUNGAN LAPANGAN TERHADAP KEMAMPUAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS X SMA SWASTA PRAYATNA MEDAN TAHUN AJARAN 2012/2013 - DEWI SAFITRI RITONGA (Kode : Jurnal Bahasa, 2014)
This study aimed to describe the technique of site visits terhadap pengaruh writingabilities paragraf description of class X High School Private Lessons PrayatnaMedaan Year 2012/2013. This study population is all private school studentskelaas X Prayatna as many as 320 people. Samples were taken at random by 600rang, 30 0rang for experimental class and 30 for grade control.The instrument used was a test to write a paragraph description. The averagevalue of the experimental class was 75.6, while for the control class is 68.6Thus, it can be said that the average value of the ability to write a paragraphdescription of the experimental class higher than the control Kellas.Hypothesis testing is performed using test test "t". Test hypotheses derived fromcalculations thitung = 4.02, further consultation with the table at the significantlevel of 5% and 1% level of significance df = (N1 + N2) - 2 = 58. In the table twith df = 58 obtained TTable at 5% significance level = 2.00 and 1% significancelevel = 2.65. Testing criteria is rejected H0 if t0> tt. From the test resultsexplained that t0 (4.02)> tt (2.65). This means that Ho is rejected.So we can conclude that learning techniques visits more influential than theexpository technique to kemampuan students in writing a paragraph descriptionKeywords: Effects, Engineering field trips, writing paragraf description